2015
DOI: 10.1007/s00234-015-1525-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy in patients with tandem stenoses

Abstract: In this issue, Lockau et al. retrospectively analyze different approaches for endovascular recanalization of tandem occlusions in acute stroke [1]. Starting with stent angioplasty of the carotid occlusion as the first step (stent-first group), they reversed the order of their techniques and performed intracranial thrombectomy prior to stenting of the carotid occlusion (thrombectomy-first group, the so-called upside-down approach). They found advantages and disadvantages with both techniques; however, time of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…These tandem occlusions do poorly with IVT alone [ 5 , 19 ], yet, due to their complex nature [ 5 ], they are often excluded from [ 2 , 5 ] or underrepresented in the large trials [ 6 ], therefore highest level of scientific evidence to support treatment options is lacking [ 3 , 19 , 20 ]. Sub-analysis of the large trials found that TO did better with MT [ 19 ], with good outcomes reported after endovascular treatment [ 2 , 5 , 21 ]. HERMES, for example, demonstrated similar outcomes for TO patients after MT to those with isolated LVO [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…These tandem occlusions do poorly with IVT alone [ 5 , 19 ], yet, due to their complex nature [ 5 ], they are often excluded from [ 2 , 5 ] or underrepresented in the large trials [ 6 ], therefore highest level of scientific evidence to support treatment options is lacking [ 3 , 19 , 20 ]. Sub-analysis of the large trials found that TO did better with MT [ 19 ], with good outcomes reported after endovascular treatment [ 2 , 5 , 21 ]. HERMES, for example, demonstrated similar outcomes for TO patients after MT to those with isolated LVO [ 2 ].…”
Section: Discussionmentioning
confidence: 99%